2009
DOI: 10.1149/1.3033498
|View full text |Cite
|
Sign up to set email alerts
|

Microelectrochemical Investigation on Pit Initiation at Sulfide and Oxide Inclusions in Type 304 Stainless Steel

Abstract: MnS and MnO inclusions with a small amount of chromium were obtained by heat-treatments of Type 304 stainless steel at 1353, 1573, and 1673 K, and the anodic dissolution behavior of the inclusions was investigated using a microelectrochemical technique. In the case of the sulfide inclusions, those with a high dissolution potential were found to provide high pitting potentials in the macroscopic measurements in 0.1 M NaCl. The initiation sites of metastable and stable pits were at the boundaries of the inclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 33 publications
1
63
0
Order By: Relevance
“…For the solution-treated specimen, many current spikes were generated above 0.4 V, and the current density rapidly increased and exceeded 0.1 A m −2 at 0.67 V. The potential region for MnS dissolution has been reported to be around 0.5 V in NaCl solutions. 13,14,[17][18][19]24 The many current spikes around 0.5 V were due to the dissolution of the sulfide inclusions, suggesting that the inclusions were likely the initiation sites for pitting. 17 In the case of the sensitized specimen, a sharp increase in the current density appeared suddenly at 0.32 V. The pitting potential of the sensitized specimens were determined to be around 0.3 V.…”
Section: Resultsmentioning
confidence: 99%
“…For the solution-treated specimen, many current spikes were generated above 0.4 V, and the current density rapidly increased and exceeded 0.1 A m −2 at 0.67 V. The potential region for MnS dissolution has been reported to be around 0.5 V in NaCl solutions. 13,14,[17][18][19]24 The many current spikes around 0.5 V were due to the dissolution of the sulfide inclusions, suggesting that the inclusions were likely the initiation sites for pitting. 17 In the case of the sensitized specimen, a sharp increase in the current density appeared suddenly at 0.32 V. The pitting potential of the sensitized specimens were determined to be around 0.3 V.…”
Section: Resultsmentioning
confidence: 99%
“…21,22 The development of this technique led to advances in the past twenty years regarding the understanding of pitting corrosion at non-metallic inclusions in stainless steels. [23][24][25][26][27][28] Chiba et al developed a micro-electrochemical system for in situ high-resolution optical microscopy, which can be used for the morphological analysis of pitting during the very beginning of the initiation process. [29][30][31] In this study, we used this technique to investigate the initiation site of pitting of AISI 1045 ferrite-pearlite steel.…”
Section: 10mentioning
confidence: 99%
“…Compared with Al 2 O 3 inclusions, pitting corrosion occurred more easily at the junction of the steel matrix and Mg, Al, Ca composite oxide inclusion. Muto et al [16] conducted pitting corrosion micro-electrochemical experiments of sulfide and oxide inclusions in 304 stainless steel. They observed that MnS/CrS inclusions were more likely to be sites of pitting initiation rather than the MnO/CrO inclusions.…”
Section: Introductionmentioning
confidence: 99%